Arte, criatividade e tecnologia na perspectiva do jovem estudante do curso Técnico em Informática Integrado ao Ensino Médio - Chaves, Mauro Ribeiro (2020)
This research aims to explore the nexuses between art, creativity and technology in the perspective of the young student of the Technical Course in Informatics Integrated to High School at IFSP. The value judgment, regarding the permanence or not of some subjects in the school curriculum, always goes through its technical function, leaving aside objectivity, subjectivity and the critical and affective development of the student. Under the guiding thread of Marcuse's concepts of technology, Teplov on art and Gulilford, from Marin's perspective on creativity, this study aims to verify and analyze, formulating new hypotheses in the light of exploratory study, the student's manifestation about the place occupied by art , creativity and technology in relation to social and school processes, in High School Integrated to the Computer Technician. In this way, the object of study are the narratives of young people collected through three instruments: an open questionnaire with five questions in which it was sought to observe the description of the student about his school trajectory; a practical activity of transposing art content to a technological support in order to reveal the links between discourse and practice; finally, the closed questionnaire with questions about art, creativity and technology that could bring the conceptual perspective of young people on the respective themes. The analyzes and considerations were conceived based on the responses of young people from the perspective of theoretical frameworks considering an exploratory research